2017
DOI: 10.1186/s12967-017-1300-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lumbar degenerative disc disease-associated radicular pain with culture-expanded autologous mesenchymal stem cells: a pilot study on safety and efficacy

Abstract: BackgroundDegenerative disc disease (DDD) is a common cause of lower back pain with radicular symptoms and has a significant socioeconomic impact given the associated disability. Limited effective conservative therapeutic options result in many turning to surgical alternatives for management, which vary in the rate of success and also carry an increased risk of morbidity and mortality associated with the procedures. Several animal based studies and a few human pilot studies have demonstrated safety and suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(146 citation statements)
references
References 73 publications
2
144
0
Order By: Relevance
“…In one pilot study using autologous bone marrow stem cell JOURNAL OF ORTHOPAEDIC RESEARCH ® JUNE 2019 injection, investigators observed a significant improvement of pain and disability in 3 months. 37 Similarly, Centeno et al 38 demonstrated that significant improvement of impairment and pain relieve in 33 patients receiving autologous BM-MSC injection though 6 years of follow up. Additionally, 85% of the patients had a reduction in disc bulge size.…”
Section: Discussionmentioning
confidence: 96%
“…In one pilot study using autologous bone marrow stem cell JOURNAL OF ORTHOPAEDIC RESEARCH ® JUNE 2019 injection, investigators observed a significant improvement of pain and disability in 3 months. 37 Similarly, Centeno et al 38 demonstrated that significant improvement of impairment and pain relieve in 33 patients receiving autologous BM-MSC injection though 6 years of follow up. Additionally, 85% of the patients had a reduction in disc bulge size.…”
Section: Discussionmentioning
confidence: 96%
“…One recent study by Centeno et al examined percutaneous injection of MSCs into in vivo human lumbar discs with hernation of the NP; they described a low complication rate, clinical improvement and decrease in the size of disc herniation on long term follow up. 20 When looking at intradiscal injection of MSCs and hyaluronic acid reported no adverse events and improved clinical outcome measures. 21 Of the improved patients, 50% had increased water content within the disc at longterm follow up, though no changes were noted in radiographic measures of disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial potential for intradiscal injectable therapeutics for treating IDD. One recent study by Centeno et al examined percutaneous injection of MSCs into in vivo human lumbar discs with hernation of the NP; they described a low complication rate, clinical improvement and decrease in the size of disc herniation on long term follow up . When looking at intradiscal injection of MSCs and hyaluronic acid scaffold in a clinical trial of 10 patients, Kumar et al reported no adverse events and improved clinical outcome measures .…”
Section: Discussionmentioning
confidence: 99%
“…Four studies analyzed the effects of intradiscal injection of MSCs. Three showed improvement in measured pain and disability scores with follow‐up periods of at least 1 year . The lone negative study showed no improvement in numeric pain scores at 1 year after intradiscal injection of BMAC‐MSCs followed by a 2‐week course of hyperbaric oxygen therapy …”
Section: Orthobiologics and The Literaturementioning
confidence: 94%